ANALISIS PEMODELAN JUMLAH PENERIMAAN PAJAK ACEH TIMUR TAHUN 2024 DENGAN MENGGUNAKAN METODE TIME SERIES - Asna, Intan Junidil; Muliani, Fitra; Amelia; Fairus, Fairus (JURNAL GAMMA-PI, 2025)
Taxes are contributions that must be paid by taxpayers to the state. Taxes are used to finance general expenses related to the state's duties in running government. In April 2020 the total tax revenue in East Aceh Regency was IDR 905,028,600.00. Tax revenues increase every year, until January 2023, namely IDR 2,240,720,100.00. This research aims to determine the prediction of the amount of tax revenue for East Aceh Regency in 2024 using the time series method. Time series is a method for predicting future events or values based on data from the past. The model used is the ARIMA model. The data used is data on the amount of tax revenue every month from January 2020 to January 2023. This data was obtained from the East Aceh One-Stop Single Administration System (SAMSAT) Office. The results of the analysis show that the total tax revenue for East Aceh in 2024 is IDR 1,662,329,757.00. The model used is the ARIMA model (1,1,1) because this model is the best model after all assumptions have been met.